Galectins and galectin-mediated autophagy regulation: new insights into targeted cancer therapy - Dan Liu; Hongtao Zhu; Chuanzhou Li (BMC, 2023)
Abstract Galectins are animal lectins with specific affinity for galactosides via the conserved carbohydrate recognition domains. Increasing studies recently have identified critical roles of galectin family members in tumor progression. Abnormal expression of galectins contributes to the proliferation, metastasis, epithelial-mesenchymal transformation (EMT), immunosuppression, radio-resistance and chemoresistance in various cancers, which has attracted cumulative clinical interest in galectin-based cancer treatment. Galectin family members have been reported to participate in autophagy regulation under physiological conditions and in non-tumoral diseases, and implication of galectins in multiple processes of carcinogenesis also involves regulation of autophagy, however, the relationship between galectins, autophagy and cancer remains largely unclear. In this review, we introduce the structure and function of galectins at the molecular level, summarize their engagements in autophagy and cancer progression, and also highlight the regulation of autophagy by galectins in cancer as well as the therapeutic potentials of galectin and autophagy-based strategies. Elaborating on the mechanism of galectin-regulated autophagy in cancers will accelerate the exploitation of galectins-autophagy targeted therapies in treatment for cancer.